Transcriptomic and Chemical Analyses Reveal the Hub Regulators of Flower Color Variation from Camellia japonica Bud Sport - Menglong Fan; Ying Zhang; Meiying Yang; Si Wu; Hengfu Yin; Jiyuan Li; Xinlei Li (Horticulturae, 2022)
Camellia japonica is a woody ornamental plant with multiple flower color variations caused by bud sport; however, the molecular mechanism remains unclear. Here, chemical and transcriptomic analyses of C. japonica were performed with white, pink, red, and dark red flowers caused by bud sport. Seven anthocyanins were detected in these samples, except in C. japonica ‘YuDan’ (white petals). The total anthocyanin content of C. japonica ‘JinBiHuiHuang’ was the highest, and cyanidin 3-O-β-glucoside (Cy3G) was the main anthocyanin affecting the redness of petals. Furthermore, the ratio of Cy3G and cyanidin-3-O-(6-O-(E)-p-coumaroyl)-B-glucoside) was significantly correlated with the red petal phenotype. In total, 5673 genes were identified as differentially expressed genes (DEGs). The potential co-expression modules related to anthocyanin accumulation were established, which featured transcription factors, anthocyanin biosynthesis, and plant hormone signal transduction. Thirteen structural genes in the anthocyanin biosynthetic pathway were identified as DEGs, most of them were upregulated with deepening of flower redness. An integrated promoter and cluster analysis suggested that CjMYB62, CjMYB52, and CjGATA may play important roles in anthocyanin accumulation. These results provide insight and candidate genes for the transcriptional mechanism responsible for the bud sport phenotype.